The Use of Interactive Educa Studio Media as an Effort to Increase Buying Introduction Ability in Supermarket for Student with Intellectual Disabilities - Puput Roshandayani (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study was to improve the ability to recognize buying and selling in supermarkets through interactive Educa studio media for students with mild intellectual disabilities. This study used classroom action research using interactive learning methods for students with mild intellectual disabilities as many as 5 students who took the test. The data collection technique in this study is a qualitative descriptive technique. We collected data based on the results of the tests imposed on respondents. Based on the results of the three cycles of action, it can be concluded that the use of Educa studio media can increase the ability to recognize buying and selling in supermarkets with an average increase in achievement of 0.5, learning achievement when compared to the initial conditions increases by an average of 1.5 from 5.00 to 6.50.